Recovering Trade Networks in the Swahili Hinterland: An Archaeological Study of the Tana Delta (Kenya) - (:unkn) unknown (My University, 2019)
The communication exhibits results of my current PhD research dealing with the circulation of items into the Tana Delta in Kenya, specifically between the merchant Swahili cities of the coast and the rural settlements within the delta. This research tries to find evidence of this link through the wide archaeological material (potteries, marine shells – cowries, imported items, imported plants and animals) putting forward the role of hinterland played by the Tana Delta for the coastal towns. Therefore my PhD studies the relationship between human and environment as the delta provided the cities in luxurious matters reserved for exportation (rhinoceros horns, ivory, mangrove wood, and spices) but also in daily needs (crops, wood, fish, potteries, etc.). All the data collected on the fieldwork and the documentation are gathered into a GIS database driving to an archaeological map which projects a reconstitution of the delta’s history during the last 2 000 years. It must provide a new reading of the past land use almost unknown involving the natural and human transformations of the area (e.g. allogenic species introduction). The trade routes from the coast to the upper part of the Tana River, reconstituted by the archaeological evidence found during surveying and test excavations, should enlighten our understanding of the past trade network in the region. Despite a large range of time I try to focus my work on the Iron Age (-100 to 1600 ca), more specifically on the medieval period from the arriving of Islam on the East-African shore to the first century of European presence in East-Africa.
Keywords: African Research